Adding value to antiretroviral proficiency testing. (October 2014) - DiFrancesco, Robin; Taylor, Charlene R; Rosenkranz, Susan L; Tooley, Kelly M; Pande, Poonam G; Siminski, Suzanne M; Jenny, Richard W; Morse, Gene D
Background : Clinical trial specimens tested for antiretroviral (ARV) concentrations often require compliance with Clinical Laboratory Improvement Act and/or the Food and Drug Administration bioanalytical guidance.Experimental: The Clinical Pharmacology Quality Assurance Program (CPQA) designed 8 proficiency testing (PT) rounds over 4 years to assess precision, specificity and stability.Results : Ten laboratories provided blinded proficiency data to support continued acceptable precision of ARV methods. Specificity samples identified little bias for individual methods; hemolyzed (87%) and lipemic (86%) results were ≤10% of their control results. Stability was established for ARVs in plasma at -70°C for 2.5–3.6 years.Conclusion : PT provided by the CPQA assured continued acceptability of individual laboratory assay performances for precision and specificity, and obtained ARV stability during long term storage.